Au rendez-vous allemand (2) - Agnès Bouvier (Flaubert: Revue Critique et Génétique)
The publication in 1857 of Ernest Renan’s Études d’histoire religieuse signals the introduction in France of German ideas about myths applied to the history of religious texts. Now this date is also that of the intellectual encounter between Renan and Flaubert. Their actual meeting came about two years later. Indeed, while Flaubert was starting Salammbô, he discovered the philological studies of the “New School” represented in France by Renan. According to Renan the superiority of the German School was due to its capacity to comprehend the myth as an undivided whole irreducible to a univocal interpretation. Thus, despite the excesses of the “rationalists” and “mythologs”, whose methods he clearly distinguished, Renan considered the German exegesis a progress. He outlined its stages which he sought to complete by developing what he called a “sympathetic” approach. Rather than a method, Renan defined a critical position of to adherence to the object, an approach which Flaubert applied to his novel.